The Synergy of Social Capital and Vocational Training: Evaluating the Sustainability of Community-Based Home Industries in Emerging Economies - Aries Purwanto; Muh Irfan Mukhlishin; Suparno Suparno; Chen Mei (Yayasan Adra Karima Hubbi, 2026)
Background. Community-based home industries play a vital role in the economic development of emerging economies, offering a source of livelihood and preserving local cultures. The synergy between social capital and vocational training is increasingly recognized as crucial for the sustainability of these industries. Social capital, encompassing networks, relationships, and trust, alongside vocational training, which enhances skills and productivity, can significantly impact the long-term success of home-based businesses. Purpose. This study aims to evaluate how the interaction between social capital and vocational training influences the sustainability of community-based home industries in emerging economies. Method. A mixed-methods approach was employed, including surveys to measure business performance and qualitative interviews to understand the role of social networks and training in business success. Results. The results reveal that firms with strong social networks and access to vocational training show higher levels of productivity, market access, and longevity. These businesses experienced up to a 30% increase in productivity and a 25% improvement in sustainability compared to those without access to both factors. Conclusion. The findings emphasize that integrating social capital with vocational training enhances the resilience of small businesses in low-resource environments, providing valuable insights for policymakers seeking to support sustainable entrepreneurship.